Integrated Strategies for Durable Rice Blast Resistance in Sub-Saharan Africa - Mutiga, Samuel Kilonzo; Rotich, Felix; Were, Vincent M.; Kimani, John M.; Mwongera, David T.; Mgonja, Emmanuel M.; Onaga, Geoffrey; Konaté, Kadougoudiou; Razanaboahirana, Claudine; Bigirimana, Joseph; Ndayiragije, Alexis; Gichuhi, Emily W.; et al. (Scientific Societies, 2021)
Rice is a key food security crop in Africa. The importance of rice has led to increasing country-specific, regional, and multinational efforts to develop germplasm and policy initiatives to boost production for a more food-secure continent. Currently, this critically important cereal crop is predominantly cultivated by small-scale farmers under suboptimal conditions in most parts of sub-Saharan Africa (SSA). Rice blast disease, caused by the fungus Magnaporthe oryzae, represents one of the major biotic constraints to rice production under small-scale farming systems of Africa, and developing durable disease resistance is therefore of critical importance. In this review, we provide an overview of the major advances by a multinational collaborative research effort to enhance sustainable rice production across SSA and how it is affected by advances in regional policy. As part of the multinational effort, we highlight the importance of joint international partnerships in tackling multiple crop production constraints through integrated research and outreach programs. More specifically, we highlight recent progress in establishing international networks for rice blast disease surveillance, farmer engagement, monitoring pathogen virulence spectra, and the establishment of regionally based blast resistance breeding programs. To develop blast-resistant, high yielding rice varieties for Africa, we have established a breeding pipeline that utilizes real-time data of pathogen diversity and virulence spectra, to identify major and minor blast resistance genes for introgression into locally adapted rice cultivars. In addition, the project has developed a package to support sustainable rice production through regular stakeholder engagement, training of agricultural extension officers, and establishment of plant clinics.